Միհրան Թումաճանի կյանքն ու գործը - Սաթենիկ Ղափլանյան (ՀՀ ԳԱԱ հրատ.)
В статье представлены жизнь и многосторонная деятельность одного из пяти учеников Комитаса – Миграна Тумаджана. Говорится о его дирижерских, музыковедческих-публицистических и фольклористических работах. In this article considers the life and many-sided undertakings of M.Toumajan, one of the five pupils of Komitas. Ghaplanyan presents his work as a music conductor, public speaker, collector and transcriber of folk music as well as his studies on musicology.
Keywords: Biography; Music